POLITICAL MARKETING STRATEGIES OF WOMAN CANDIDATES TO WIN THE 2019 PROVINCIAL LEGISLATIVE ELECTION IN CENTRAL JAVA - Yufanabila Risma; Dian Eka Rahmawati (Jurnal Pemerintahan dan Kebijakan (JPK), 2020)
The political marketing strategy of legislative candidates is one of the important roles for the victory of a legislative candidate. This study aims to find out how Siti Ambar Fathonah S.Pd.I Political Marketing Strategy to Win the 2019 Legislative Election in Central Java. The research method used is qualitative research with a descriptive approach. Data collection techniques through interviews and documentation. The results of the study show that the marketing strategy carried out by Siti Ambar Fathonah has been going well with push marketing and pull marketing strategies that are used optimally in approaching the community. This marketing success brought him back to the legislative seat for the 2019-2024 period. However, it is not maximized in pass marketing, namely the use of social media as an arena for campaigning to the public. The 2019 Central Java provincial election is proof that political marketing plays an important role for Siti Ambar in gaining votes in the Golkar faction's electoral district II which brought her to the seat of the Central Java Provincial DPRD for the 2019-2024 period.